KEHIDUPAN PENGEMUDI BECAK MOTOR DI KUALU PANAM KECAMATAN TAMPAN KOTA PEKANBARU - ", Suzana; ", Risdayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted at Jalan Suka Karya District of Tampan, Pekanbaru City. The purpose of this study was to find out how the profile and survival strategies of motorized rickshaw drivers in meeting economic needs. The theory used in this research is to use rational choice theory and survival strategies. Data analysis techniques used by researchers to answer the problem formulation in this study using qualitative research methods using a descriptive approach which is then analyzed based on theory and presented in the form of narrative qualitatively. The data collection technique in this study used a purposive sampling technique in which informants were selected according to certain criteria where the results were 11 people. Based on the results of research in the field of motorized rickshaw drivers rational choose to stay as a motorized rickshaw driver by establishing three strategies for survival namely an active strategy that optimizes family potential by having side jobs and family members who also work, passive strategies that minimize expenses in terms of clothing, food , health and family education, most recently a network strategy by building relationships and utilizing existing poverty programs from the government.Â Â Keywords: Survival Strategies, Motorized Rickshaw Drivers Â